Methods for detecting the cassava bacterial blight pathogen : A practical approach for managing the disease - Verdier, Valerie M.; Ojeda, S; Mosquera Cifuentes, Gloria Maria (Springer, 2001)
Cassava bacterial blight (CBB), caused by Xanthomonas axonopodis pv. manihotis (Xam), is a particularly destructive disease in South America and Africa. The movement of infected asymptomatic stems is a major means of pathogen dispersal as well as infected seeds. The success of a cassava-seed certification program depends on the availability of reliable tests to detect the pathogen in vegetative planting materials and true seeds. We report here the different methods that permitted to detect the pathogen in cassava tissues. A polymerase chain reaction (PCR) test was developed for this pathogen. The PCR assay worked well for pathogen detection in extracts from leaf and stem lesions and the minimum number of cells that could be detected ranged from 3 × 102 to 104 CFU per ml. Nested-PCR worked well for Xam detection from naturally infected seeds. This technique was specific, sensitive, and rapid for detecting Xam in cassava true seeds. The highest detection level found was 1 2 viable cells per reaction. A dot-blot assay was developed by evaluating a 898 bp DNA fragment unique to Xam strains as a diagnostic DNA probe. The probe detected Xam strains in crude extracts of leaf and stem lesions, cassava fruits and sexual seeds that were naturally infected. Overall sensitivity of the dot-blot method was about103CFU per reaction. The dot-blot hybridization technique can be easily used for culture indexing. A monoclonal antibody (MAb) was also used for an enzyme-linked immunosorbent assay (ELISA) and tested with various infected tissues. Overall sensitivity of the method was about103CFU per reaction.